Electronic Procurement Negotiation process from an Actor Network Theory Perspective - Alaweti, Mohamed Fathi; Azizan, Nurdiana; Faryadi, Qaise (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The paper presents a case study of the use of existing electronic procurement (E-procurement) negotiations processes. It focuses on reviewing the negotiations processes that the system introduces. It, then, applies the Actor Network Theorys (ANT) notions of associations and power in order to illustrate that the negotiations processes introduce a new power circuit effect. In so doing, it aims to provide insight into the performing strong relation in social and technical of both human and non-human actors network that the newly introduced system negotiations processes constructs. A qualitative data method applied in this study, then it suggests that the E-procurement system should negotiation processes would affect the social and organisational architecture of the organisation and its established performing power networks.